Pamphlet beginning 'Le premier billet, qu'aye jamais receu le Sieur Rangeard, par l'ordre de la Compaignie de Messieurs les Medecins jurés de Bordeaux, est suivant, écrit et signé de la main de Mr Audat, ausse Medecin juré, le cinquiéme Novembre 1680.' - Rangeard, Jean (s.l : s.n, 1683)
Evidence of Rangeard's position as physician in Bordeaux. Pages 1-4: 'billets' (in French) received by Rangeard's demonstrating his membership of the Compaignie de Messieurs les Medecins jurés de Bordeaux and years of practice as a physician. Pages 5-7: convening of the Compaignie de Messieurs les Medecins jurés de Bordeaux (in Latin).
Previously catalogued as 'pamphlet about "Rangeard docteur en médecine", [no date].'
No annotations.
With: four pamphlets on the legal case concerning Jean Rangeard's exclusion from practicing medicine in Bordeaux in 1684; two pamphlets related to Élie Bouhéreau's exclusion for the medical college in La Rochelle, kept by Élie Bouhéreau together with two letters from Rangeard dated 28th October and 10th November 1684 and the original envelope [from Rangeard]
French and Latin.